2009
DOI: 10.1007/s12016-009-8134-1
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Hyper IgE Syndrome

Abstract: Hyper IgE syndrome (HIES) is a rare primary immunodeficiency characterized by the triad of elevated IgE and eosinophilia, eczema, and recurrent skin and pulmonary infections. The autosomal dominant (AD) form of HIES results from mutations in STAT3 and is characterized by disordered inflammation, connective tissue, and skeletal abnormalities. Tissue-specific STAT3 deficiency in animals, cytokine and transcriptional array data, and careful clinical phenotyping have explained some of the pathophysiology of the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 55 publications
1
76
0
3
Order By: Relevance
“…3,4,7 Viral skin infections most commonly seen are severe and sometimes mutilating infections with Herpes simplex, Varicella zoster, Molluscum contagiosum, and human papilloma virus, which are often diffuse and resistant to usual therapies. 5,8,9,10 Some authors have reported efficiency of topical cidofovir for recalcitrant molluscum contagiosum in immunocompromised children. The facies described in AD-HIES are found in recessive forms but are less marked.…”
Section: Geneticsmentioning
confidence: 99%
“…3,4,7 Viral skin infections most commonly seen are severe and sometimes mutilating infections with Herpes simplex, Varicella zoster, Molluscum contagiosum, and human papilloma virus, which are often diffuse and resistant to usual therapies. 5,8,9,10 Some authors have reported efficiency of topical cidofovir for recalcitrant molluscum contagiosum in immunocompromised children. The facies described in AD-HIES are found in recessive forms but are less marked.…”
Section: Geneticsmentioning
confidence: 99%
“…The most characteristic facial feature is a broad nasal base and broad nasal bridge, protrusion of the forehead, wide outer canthal distances, and deep set eyes [6,7] .…”
Section: Discussionmentioning
confidence: 99%
“…Description: Hyper-IgE Syndrome (HIES) represents a group of disorders characterized by recurrent skin and lung infections, eczema, and elevated IgE levels (Heimall et al 2010). An autosomal dominant form (OMIM# 147060), also known as Job's Syndrome, is associated with distinctive coarse facial features, delayed shedding of primary teeth, frequent bone fractures, spinal deformities, vascular anomalies, and development of lymphoma (Heimall et al 2010).…”
Section: Hyper-ige Syndromesmentioning
confidence: 99%
“…An autosomal dominant form (OMIM# 147060), also known as Job's Syndrome, is associated with distinctive coarse facial features, delayed shedding of primary teeth, frequent bone fractures, spinal deformities, vascular anomalies, and development of lymphoma (Heimall et al 2010). Pulmonary infections often result in pneumatoceles and (or) bronchiectasis.…”
Section: Hyper-ige Syndromesmentioning
confidence: 99%